Anesthetic management for resection of a giant emphysematous bulla: a case report - Lin, Xianju (J Int Med Res, 2021)
Anesthetic management for patients with a giant emphysematous bulla (GEB) is challenging. This case report describes a patient who developed 95% pulmonary compression by a GEB. A 14-Ga indwelling catheter was placed in the GEB before surgery to allow for slow re-expansion of the collapsed lung tissue. This prevented rupture of the GEB during anesthesia. Additionally, positive-pressure ventilation was performed to reduce the risk of re-expansion pulmonary edema. This respiratory management strategy may be beneficial for patients with a GEB who develop pulmonary dysfunction during thoracic surgery.